Design of high gain dual T-shaped stub antenna for satellite communication - Aylapogu Pramod Kumar; D. M. K. Chiatanya; D. Venkatachari (Universitas Ahmad Dahlan, 2020)
The ultra wide band (UWB) antennas play a vital role in supporting different wireless standards and are suitable for wide variety of applications. This paper is aimed to present a novel UWB dual notch microstrip antenna with modified ground plane. The antenna is designed to operate in UWB ranging from 2 GHz to 12 GHz with multi band operation. This will help in operating the antenna for different operations independently. The proposed structure will operate in two notch bands 3.3-4 GHz (Wi-MAX), 5.05-5.9 GHz (WLAN) and the structure is suitable for long distance communications because of its increased directivity. The structure can also be used for X-Band applications for various applications of traffic control, weather forecasting and vehicle speed detection systems. It is observed that, the proposed structure is offering a gain of 5.2 dBi with improved directivity with a beam width of 42.230. This makes the antenna structure suitable for long distance satellite communications. The antenna is supporting the circular polarization at higher the frequencies and can be useful for the upcoming 5G mobile applications. Moreover, the proposed structure offers the less interference at the receiver. The structure is found to be smaller in dimensions, easily fabricated at low costs and can be integrated into any compact wireless devices. The structure is simulated using a commercially available software Ansys-HFSS and is analyzed.